Analysis of Leadership Influence, Resource Allocation, and Employee Engagement on The Effectiveness of Strategy Implementation - Ade Aziz Kusnaya; Syukri Lukman; Syafrizal Syafrizal (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2022)
This study aims to analyze the effect of leadership, resource allocation and employee engagement on the effectiveness of strategic implementation with organizational commitment as a mediating variable. The amount of sample is 52 employees with sampling technique is saturated sampling method. This study uses path analysis SEM (Structural Equation Modeling) which is processed with the IBM SPSS AMOS V23 program. The results show that leadership has a direct insignificant effect on organizational commitment, resource allocation has a direct and insignificant effect on organizational commitment, employee engagement has a direct influence on organizational commitment, leadership has a direct influence on the effectiveness of strategy implementation, resource allocation has a direct influence on organizational commitment. not directly significant on the effectiveness of strategy implementation, Employee engagement has a significant direct effect on the effectiveness of strategy implementation, Organizational commitment has a significant direct effect on the effectiveness of strategy implementation, Organizational commitment is unable to mediate the influence of leadership on the effectiveness of strategy implementation, Organizational commitment is unable to mediate the influence of resource allocation power on the effectiveness of strategy implementation, organizational commitment is able to mediate the effect of employee engagement on effectiveness of strategy implementation.